New Zealand : 2007 Article IV Consultation; Staff Report; Public Information Notice; and Statement by Executive Director for New Zealand on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that the economic downturn of New Zealand that commenced in 2005 has proved to be short lived. In early 2006, the economy appeared to be cooling quickly, with quarterly growth dropping to zero and confidence and demand indicators deteriorating. Some needed rebalancing of the economy took place. Over the last few months, the cycle has turned again. A range of indicators in late 2006 and early 2007 suggest that domestic demand has regained momentum. These include a resurgent housing market and improved business and consumer confidence.